The roles of community seed banks in climate change adaption - Vernooy, Ronnie; Sthapit, B.R.; Otieno, G.; Shrestha, P.; Gupta, A. (Informa UK Limited, 2017)
Although community level seed-saving initiatives have been around for about 30 years, until recently they have received little attention in the scientific literature on climate change adaptation and plant genetic resources. Based on research experiences from various countries, this article argues that community seed banks can enhance the resilience of farmers, in particular of communities and households most affected by climate change. Community seed banks can secure improved access to, and availability of, diverse, locally adapted crops and varieties, and enhance related indigenous knowledge and skills in plant management, including seed selection, treatment, storage, multiplication, and distribution.